Application of the Victim-Offender Overlap on a Prison Population: Findings from Official Records of Misconduct - Clark, Valerie A. (Victims & offenders, 2025)
The criminological literature has long recognized that victims and perpetrators of violence are often the same people. A limited number of studies have extended research on the victim-offender overlap to incarcerated populations using survey data measuring self-reports of victimization and offending behaviors. This study used official misconduct data from one state’s entire prison system to examine the overlap between victims and offenders in prison. Based on a sample of more than 8,000 incarcerated persons observed over a four-year period, this research identified distinct groups of only-victims, only-offenders, overlap between victims and offenders, and incarcerated persons not involved in violence at all. Age was the only consistent measure that impacted all forms of institutional violence. Other measures that had varying effects on involvement in institutional violence included sex, offense type, educational attainment, and participation in pro-social activities, among other measures. The similarities between studies of the victim-offender overlap in prison using survey data and official reports of misconduct are discussed.